IMPLEMENTASI SISTEM REWARD TERHADAP KINERJA ORGANISASI PADA UKOR UIN SUNAN AMPEL SURABAYA - Jesica , Nabilah Ayu; Prismawati, Nadiva; Bahirah, Naurah Qud's (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the impact of the reward system on organizational performance at the Sports Activity Unit (UKOR) of UIN Sunan Ampel Surabaya. An effective reward system is considered a key factor in motivating members to achieve optimal performance. The study uses a qualitative method with a survey approach, gathering data through interviews with UKOR members. The results show that the salary and incentives do not reflect the responsibilities, are inadequate, and inconsistent, which negatively affects motivation. While sports facilities support performance, limitations, especially in health benefits, hinder productivity. The lack of interpersonal recognition and unstructured feedback also reduces morale and performance. The study recommends improving the reward system and enhancing facilities to boost organizational performance.